Study on Lycopene accumulation in Difference Fruits - Theeranat Suwanaruang (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
Lycopene is a compound that has gained attention for its reported health benefits. especially reducing the risk of cancer in various organs The most obvious is prostate cancer, followed by lung and stomach cancer. It has also been shown to benefit lycopene in reducing the risk of pancreatic, colon, rectal, pharyngeal, oral, and breast cancers. Milk and mouth. This study objective is to determine lycopene content in fresh fruits, including tomatoes (Solanum Lycopersicum), watermelons (Citrullus lanatus var. lanatus), jackfruits (Artocarpus heterophyllus), bananas (Musa acuminata), grapes (Vitis vinifera), oranges (Citrus reticulata), and papayas (Carica papaya). The results found that lycopene in tomatoes (Solanum Lycopersicum), watermelons (Citrullus lanatus var. lanatus), jackfruits (Artocarpus heterophyllus), bananas (Musa acuminata), grapes (Vitis vinifera), oranges (Citrus reticulata), and papayas (Carica papaya) were 104.699±0.000, 144.27±0.001, 4.122±0.000, 31.189±0.001, 10.028±0.000, 13.1904±0.000 and 45.342±0.000 mg/kg, respectively. Watermelons (Citrullus lanatus var. lanatus) had the most lycopene, whereas jackfruits (Artocarpus heterophyllus) had the least. Lycopene (Lycopene) is a red substance found in some fruits and vegetables. And is an antioxidant that is a subunit of carotenoids. (Carotenoids), lycopene is known as a nutrient that is beneficial to health. especially skincare.